2008
DOI: 10.1128/jvi.02326-07
|View full text |Cite
|
Sign up to set email alerts
|

A Hepatitis C Virus cis -Acting Replication Element Forms a Long-Range RNA-RNA Interaction with Upstream RNA Sequences in NS5B

Abstract: The genome of hepatitis C virus (HCV) contains cis-acting replication elements (CREs) comprised of RNA stem-loop structures located in both the 5 and 3 noncoding regions (5 and 3 NCRs) and in the NS5B coding sequence. Through the application of several algorithmically independent bioinformatic methods to detect phylogenetically conserved, thermodynamically favored RNA secondary structures, we demonstrate a longrange interaction between sequences in the previously described CRE (5BSL3.2, now SL9266) with a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
157
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(168 citation statements)
references
References 39 publications
9
157
2
Order By: Relevance
“…3, purple boxes). Five elements correspond to regulatory motifs that have been well characterized: the IRES domains II-IV, SL9098, and CRE (13)(14)(15)(16)(17). We focused on the four uncharacterized RNA elements (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, purple boxes). Five elements correspond to regulatory motifs that have been well characterized: the IRES domains II-IV, SL9098, and CRE (13)(14)(15)(16)(17). We focused on the four uncharacterized RNA elements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Translation produces a viral polyprotein that is cleaved by cellular and viral proteases to generate 10 viral proteins (4). The HCV genome is replicated through a negative-strand RNA intermediate by a viral RNA-dependent RNA polymerase (NS5B) in a process controlled by conserved RNA elements (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…We have shown that the closed conformation stimulates HCV IRES initiated translation (Tuplin and others, unpublished results) and the open structure preferentially binds cellular protein EWSR1 upregulating genome replication (Oakland et al, 2013). It has been suggested that SL9266/PK functions in the temporal control of early translation and replication events (Diviney et al, 2008;Oakland et al, 2013). However, much remains to be understood regarding this complex mechanism of dynamic RNA-RNA and RNA-protein interactions, in particular how alternative conformations are stabilized and interact with different trans-activating factors.…”
Section: Initiationmentioning
confidence: 99%
“…It has been postulated that the S-fragment is involved in genome replication and that the alternative mutually exclusive long-range interactions represent a mechanism modulating FMDV translation and replication (Serrano et al, 2006). -Herranz, 2012) and that with the 9110 region essential for virus replication (Diviney et al, 2008). The terminal-loop of SL9266 forms a 'kissing-loop' interaction with stem loop SL9571 (alternatively SL2) in the 39NCR (Friebe et al, 2005).…”
Section: Initiationmentioning
confidence: 99%
“…The hairpin-loop sequence on 5BSL3.2 and the sequence on the loop of the 39-X (39SL2) have the potential to form a pseudoknot, which is regarded as essential for viral replication. In addition, a more recent study by Diviney et al (2008) provided evidence that the long range RNA interaction between 5BSL3.2 and its approximately 200 base upstream CGGG motif is also important for viral replication.…”
mentioning
confidence: 99%